2016
DOI: 10.1177/0165025415621971
|View full text |Cite
|
Sign up to set email alerts
|

Is self-regulation “All in the family”? Testing environmental effects using within-family quasi-experiments

Abstract: Most of the individual difference variance in the population is found within families, yet studying the processes causing this variation is difficult due to confounds between genetic and nongenetic influences. Quasi-experiments can be used to test hypotheses regarding environment exposure (e.g., timing, duration) while controlling for genetic confounds. To illustrate, two studies of cognitive self-regulation in childhood (i.e., working memory [WM], effortful control [EC], attention span/persistence [A/P]) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Most studies have found no evidence for systematic differences in children raised by adoptive parents and children raised by their biological parents (Knopik et al, 2017). There is, however, evidence for a restricted range of adoptive family environments with limited representation of the riskier end of the spectrum (e.g., C. H. Burt & Simons, 2014;Deater-Deckard, 2016;Stoolmiller, 1999). Research testing the effects of this range restriction on a few key constructs (delinquency, drug use, and IQ) using the strategies proposed by Stoolmiller (1999) found that the restricted range for the adoptive family environment did not have a meaningful effect on correlations between adoptive siblings (McGue et al, 2007).…”
Section: Limitations Of Genetically Informed Designsmentioning
confidence: 99%
“…Most studies have found no evidence for systematic differences in children raised by adoptive parents and children raised by their biological parents (Knopik et al, 2017). There is, however, evidence for a restricted range of adoptive family environments with limited representation of the riskier end of the spectrum (e.g., C. H. Burt & Simons, 2014;Deater-Deckard, 2016;Stoolmiller, 1999). Research testing the effects of this range restriction on a few key constructs (delinquency, drug use, and IQ) using the strategies proposed by Stoolmiller (1999) found that the restricted range for the adoptive family environment did not have a meaningful effect on correlations between adoptive siblings (McGue et al, 2007).…”
Section: Limitations Of Genetically Informed Designsmentioning
confidence: 99%
“…In this special section, our goal was to bring together studies that examine the unique role of environmental experiences on children's and adolescents' cognitive, emotional, and behavioral development while accounting for possible rGE. To achieve this goal, the studies in this special section (i.e., Barnes et al;Chen, Yu, & Zhang;Deater-Deckard;all 2016) used the so-called MZ-difference method. Since MZ (i.e., monozygotic) twins share 100% of their genes (and the same family environment when raised together), the MZ difference method affords a unique opportunity to examine the role of environmental experiences that are unique to each twin in a pair, while controlling for genetic influences (and environmental influences that are common to both twins in a pair).…”
mentioning
confidence: 99%
“…In addition to the MZ difference method, two studies in this special section (Barnes et al;Deater-Deckard;2016) also utilized other approaches in order to statistically or methodologically control for genetic confounds. Specifically, in one of the two studies described by Deater-Deckard ( 2016), the use of relative differences as an analytical strategy is extended to adoptive siblings who grow up together in the same family.…”
mentioning
confidence: 99%